Qualitative test of formalin content in Hainanese Chicken Rice in Tanjungpinang City Area - Zaleha; Simbolon, Veronika; Erda, Zulya (Talenta Publisher, 2025)
Food safety is an important issue in Indonesia that is often associated with cases of food poisoning, one of which is due to the use of banned Food Additives (BTP) such as formalin. The people of Tanjungpinang City consume a lot of processed chicken meat, such as Hainanese chicken rice, so it is important to ensure its quality and safety. This study aims to identify the organoleptic physical quality of chicken meat and detect the presence of formalin in Hainanese chicken rice. This type of research is descriptive qualitative with an observational approach. The study population included all Hainanese chicken rice traders in Tanjungpinang City as many as 51 people, and all were sampled (total sampling). The physical examination of chicken meat was conducted organoleptically, while the formalin content test used potassium permanganate solution (KMnO₄). Results showed that formalin-positive chicken meat is characterized by its off-white color, pungent odor, and chewy texture. Of the 51 samples tested, 11 showed positive results for formalin, indicated by a change in color to cloudy yellow or brown. Meanwhile, negative samples showed a pink color with no significant color change. These findings emphasize the importance of monitoring the use of formaldehyde in ready-to-eat food.